What is the Rate of Revision Discectomies After Primary Discectomy on a National Scale?. Issue 11 (November 2017) - Virk, Sohrab S.; Diwan, Ashish; Phillips, Frank M.; Sandhu, Harvinder; Khan, Safdar N.
Abstract: Background: Lumbar discectomy has been shown to be clinically beneficial in numerous studies for appropriately selected patients. Some patients, however, undergo revision discectomy, with previously reported estimates of revisions ranging from 5.1% to 7.9%. No study to date has been able to precisely quantify the rate of revision surgery over numerous years on a national scale. Questions/Purpose: We performed a survival analysis for lumbar discectomy on a national scale using a life‐table analysis to answer the following questions: (1) What is the rate of revision discectomy on a national scale over 5 to 7 years for patients undergoing primary discectomy alone? (2) Are there differences in revision discectomy rates based on age of patient, region of the country, or the payer type? Methods: The Medicare 5% National Sample Administrative Database (SAF5) and a large national database from Humana Inc (HORTHO) were used to catalog the number of patients undergoing a lumbar discectomy. Both of these databases have been cited in numerous peer‐reviewed publications during the previous 5 years and routinely are audited by PearlDiver Inc. We identified patients using relevant ICD‐9 codes and Current Procedural Terminology (CPT) codes, including ICD‐9 72210 (lumbar disc displacement) for disc herniation. We used appropriate CPT codes to identify patients who had a lumbar discectomy. We analyzed patients undergoing additional surgery including those who had repeat discectomy (CPT‐63042: laminotomy, reexploration single interspace, lumbar) and patients who had additional more‐extensive decompressive procedures with or without fusion after their primary procedure. Revision surgery rates were calculated for patients 65 years and older and those younger than 65 years and for each database (Humana Inc and Medicare). Patients from the two databases also were analyzed based on four distinct geographic regions in the United States where their surgery occurred. There were a total of 7520 patients who underwent a lumbar discectomy for an intervertebral disc displacement with at least 5 years of followup in the HORTHO and SAF5 databases. We used cumulative incidence of revision surgery to estimate the survivorship of these patients. Results: In the HORTHO (2613 patients) and SAF5 (4907 patients) databases, 147 patients (5.6%; 95% CI, 1.8%‐9.2%) and 305 patients (6.2%; 95% CI, 3.5%‐8.9%) had revision surgery at 7 years after the index discectomy respectively. Survival analysis showed survival rates greater than 93% (95% CI, 91%‐98%) for all of the cohorts for a primary discectomy up to 7 years after the surgery. The survivorship was lower for patients younger than 65 years (93% [95% CI, 87%‐99%, 1016 of 1091] versus 95% [95% CI, 90%‐100%, 1450 of 1522], p = 0.02). When nondiscectomy lumbar surgeries were included, the survivorship of patients younger than 65 years remained lower (83% [95% CI, 76%‐89%, 902 of 1091] versus 87% [95% CI, 82%‐92%, 1324 of 1522], p = 0.02). There was no difference in revision discectomy rates across geographic regions (p = 0.41) at 7 years. Similarly, there was no difference in additional nondiscectomy lumbar surgery rates (p = 0.68) across geographic regions at 7 years. There was no difference in survivorship rates between patients covered by Medicare (94% [95% CI, 91%‐97%], 4602 of 4907) versus Humana Inc (94% [95% CI, 90%‐98%], 2466 of 2613) (p = 0.31). Conclusions: Our study shows rates of cumulative survival after an index lumbar discectomy with revision discectomy as the endpoint. We hope these data allow physicians to offer accurate advice to patients regarding the risk of revision surgery for patients of all ages during 5 to 7 years after their index procedure to enhance shared decision making in spinal surgery. These data also will help public policymakers and accountable care organizations accurately allocate scarce resources to patients with symptomatic lumbar disc herniation. Level of Evidence: Level III, therapeutic study.